Penegakan Hukum Pembatasan Sound Pressure Level Pada Karnaval Sound System - Wijaya, Indra (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2022)
The protection of human rights and just welfare are Indonesia's orientation as a rule of law country. In line with developments and civilization, parade activities that should show our customary wealth and cultural identity are beginning to be eroded by sound system parades which tend to cause social problems in society, conflicts and even physical damage and health problems caused by the loud sound of a powerful sound system. The purpose of this study is to discuss law enforcement against limiting sound pressure levels in the hope that new arrangements can be realized. The research uses a normative juridical method with a qualitative aPeraturan Pemerintahroach that is descriptive in Law No. 32 of 2009 concerning Environmental Protection and Management. From the research conducted, findings were obtained based on statutory regulations No. 32 of 2009 regarding the enforcement of sound pressure level restrictions that have been regulated and emphasized by Peraturan Pemerintah No. 48 of 1996 concerning noise level standards and Peraturan Pemerintah No. 60 of 2017 concerning procedures for licensing and monitoring crowd activities general up to the Chief of Police's field instructionsÂ No. Pol / 02 / XII / 95 regarding licensing and notification of community activities cannot yet be implemented. Found in the Chief of Police's field instructions No. Pol / 02 / XII / 95 has not been clearly regulated regarding licensing, it only lists parade activities but there are no further arrangements.